Higher Education of Government Science in Indonesia - Nugroho, Sapto Setyo (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This paper aims to review the object of study and learning design of Government Science in Indonesia through an examination of the vision, distinctiveness, graduate profile, and curriculum of higher education institutions, as well as through study programs, as outlined by academic and educational authorities. This study examines the discourse on the development of Government Science in Indonesia, which has been widely discussed by epistemic communities, including study program associations and learner discussion forums. The method used is a desk study of curriculum documents, focusing on 13 undergraduate (S1) Government Science Study Programs that are ranked “Unggul” (Excellent) or accredited "A". The analysis areas cover the vision, distinctiveness, graduate profile, and curriculum of the study programs. The results of the review indicate that higher education institutions have formally incorporated the discourse on the development of government science; however, the curriculum review reveals a strong tendency to use the nomenclature "politics and government" in addition to the term "governance". Higher education institutions, as dual authorities, risk scientific bureaucratization and becoming trapped in ontologism. Therefore, substantial transformation is needed so that Government Science is treated as a scientific enterprise, not just an educational commodity. Higher education institutions must also escape the trap of ontologism by strengthening axiology and epistemology, with the goal of building a critical, reflective, and people-centered scientific framework.